P516 Efficacy and safety of tofacitinib retreatment for ulcerative colitis after treatment interruption: Results from the OCTAVE clinical trials. (16th January 2018) - Panés, J; Bressler, B; Colombel, J -F; Lawendy, N; Maller, E; Zhang, H; Woodworth, D A; Chan, G; Salese, L; Su, C
Abstract: Background: Tofacitinib is an oral, small-molecule Janus kinase inhibitor that is being investigated for ulcerative colitis (UC). It is not expected to elicit neutralising anti-drug antibodies that may limit successful retreatment after treatment interruption. We evaluated tofacitinib retreatment efficacy and safety after treatment interruption in patients with UC in an ongoing, open-label, long-term extension (LTE) study (OCTAVE Open, NCT01470612; data as of July 2016 [efficacy], December 2016 [safety]). Methods: OCTAVE 1 included induction (OCTAVE Induction 1 and 2), maintenance (OCTAVE Sustain) and LTE (OCTAVE Open) studies. OCTAVE Open included non-responders from OCTAVE Induction 1 and 2 and patients who completed or experienced treatment failure in OCTAVE Sustain. This analysis included the subpopulation of patients in OCTAVE Open who achieved clinical response following 8 weeks of induction therapy with tofacitinib 10 mg twice daily (BID), entered OCTAVE Sustain receiving placebo and experienced treatment failure between Week 8 and up to Week 52, and subsequently entered OCTAVE Open and received tofacitinib 10 mg BID. Treatment failure was defined as increase ≥3 points from maintenance study baseline total Mayo score plus increase in rectal bleeding subscore and endoscopic subscore (ES) ≥1 point and absolute ES ≥2 points after ≥8 weeks of maintenance therapy. We evaluated clinical response, mucosal healing and remission at Months 2 and 12 of OCTAVE Open using non-responder imputation, and evaluated safety throughout the study. Results: Of 914 patients enrolled in OCTAVE Open and treated for ≥2 months at data cut-off, 101 entered OCTAVE Open with clinical response to tofacitinib 10 mg BID in OCTAVE Induction 1 or 2 and treatment failure with placebo during OCTAVE Sustain. After entering OCTAVE Open on tofacitinib 10 mg BID, clinical response, mucosal healing and remission rates were, respectively, 75.8%, 55.4%, and 40.4% at Month 2, and 67.5%, 53.6%, and 43.4% at Month 12 (Table). Safety in the retreatment subpopulation was generally consistent with the overall study population. 2 Conclusions: In patients with prior response to tofacitinib, retreatment with 10 mg BID following a period of treatment interruption was efficacious and well-tolerated, with clinical response recaptured in approximately three-quarters of patients by Month 2 and generally sustained at Month 12 with no new safety signals. Interpretation of adverse event rates is limited due to the small sample size. References: 1. Sandborn WJ et al . Tofacitinib as induction and maintenance therapy for ulcerative colitis. N Engl J Med, 2017;376:1723–36. 2. Lichtenstein GR et al . Tofacitinib, an oral janus kinase inhibitor, in the treatment of ulcerative colitis: open-label, long-term extension study. Am J Gastroenterol, 2017;112: Abstract 714.